Play for me - Hubscher, Libby (Berkley Romance, 2023)
"When an athletic trainer loses everything she's been working toward all in one day, she decides to start over at a boarding school in this new home-run romance from the author of If You Ask Me Sophie Doyle has her dream job as the head athletic trainer for her favorite baseball team (go Red Sox!), a handsome boyfriend, and easy access to the finest cannoli in Boston. When she loses all three and the World Series to boot, she's forced to apply for the open trainer position at an arts-focused boarding school in New Hampshire. The only available room is a glorified closet in an apartment with three guys: Jonas Voss, the aloof and attractive orchestra teacher, and his two rambunctious roommates. Sophie knows that training a bunch of privileged high school kids whose idea of a play is A Chorus Line instead of a walk-off homer is going to be a big change from the pro athletes she's used to. She wasn't expecting that these students would have big-time talent and even bigger-time problems. Sophie has troubles of her own-Jonas is a full-fledged grump who clearly doesn't want her near him or the precious piano he never plays. With sunny optimism, Sophie sets out to win over Jonas and help the kids she's growing attached to. But when her relationship with Jonas moves to the major leagues and plans change at the end of the season, they have to choose whether they are playing for keeps"--